(untitled) (Revista de Artes Marciales Asiáticas, 2012)
The purpose of this study is to explain the revival of Polish martial arts from the perspectives of cultural sociology, the sciences of physical culture, and the humanistic theory of martial arts. The Polish Martial Arts (Polskie Sztuki Walki) are a subject still requiring serious scientific examination, even in Poland. There are few works concerning the history of Polish weapons, and most only describe techniques for wielding specific types of edged weapons. Nevertheless, there is a large group of enthusiasts trying to restore and cultivate the old Polish tradition, a tradition with heavy emphasis on the art of fencing. The author knows many of the people and facts presented here, from personal observation and from direct participation in these arts. As a disciple of the late Master Yoshio Sugino (10th-dan Kobudo Katori Shinto-ryu), he fought against the Polish saber champion, and he has taken part in joint exhibitions of Polish and Japanese fencing.